A Rhinological Emergency: Button Battery in the Nasal Cavity - Ferreira, Joana; Aguiar, Cristina; Gerós, Sandra; Faria de Almeida, António; Alves, Sandra; Condé, Artur (Gazeta Médica, 2021)
Foreign bodies in the nose are frequent causes of emergency care, especially in pediatric patients. In most cases they are harmless and can remain for several days without causing injury. Button batteries being an exception, pose a major threat and need urgent removal. We describe the case of a 4-year-old child seen in the Emergency Department with a suspected foreign body in the nasal cavity. She presented nasal obstruction and bloody unilateral rhinorrhea, with 5 hours of evolution. Radiography of the nasal bones identified a round, radiopaque object with a double halo sign. Upon suspicion of a button battery in the nose, it was immediately removed under general anesthesia. We intend to alert to the hazards of this type of object, as well as the need for a quick diagnostic and therapeutic approach, in order to avoid serious complications.